The language void 10 years on: multimodal primate communication research is still uncommon. Issue 3 (4th May 2022) - Liebal, Katja; Slocombe, Katie E.; Waller, Bridget M.
Abstract : Human language is thought to have evolved from non-linguistic communication systems present in the primate lineage. Scientists rely on data from extant primate species to estimate how this happened, with debates centering around which modality (vocalization, gesture, facial expression) was a likely precursor. In 2011, we demonstrated that different theoretical and methodological approaches are used to collect data about each modality, rendering datasets incomplete and comparisons problematic. Here, 10 years later, we conducted a follow-up systematic review to test whether patterns have changed, examining the primate communication literature published between 2011 and 2020. In sum, despite the promising progress in addressing some gaps in our knowledge, systematic biases still exist and multimodal research remains uncommon. We argue that theories of language evolution are unlikely to advance until the field of primate communication research acknowledges and rectifies the gaps in our knowledge.